Electrically Conductive, Reduced Graphene Oxide Structures Fabricated by Inkjet Printing and Low Temperature Plasma Reduction. Issue 12 (25th October 2019) - Sui, Yongkun; Hess‐Dunning, Allison; Wei, Peiran; Pentzer, Emily; Sankaran, R. Mohan; Zorman, Christian A.
Abstract: Here, an environmentally‐friendly and scalable process is reported to synthesize reduced graphene oxide (RGO) thin films for printed electronics applications. The films are produced by inkjet printing GO flakes dispersed binder‐free in aqueous solutions followed by treatment with a nonthermal, radio‐frequency (RF) plasma containing only argon (Ar) gas. The plasma process is found to heat the substrate to temperatures no greater than 138 °C, enabling RGO to be printed directly on a wide range of temperature‐sensitive substrate materials including photo paper. Unlike other low‐temperature methods such as electrochemical reduction, plasma reduction is friendly to moisture absorbent materials. Moreover, the plasma treatment can be performed on nonconducting substrates, eliminating the need for film transfer. From an applications perspective, the printed, plasma‐reduced RGO exhibits excellent electrical, mechanical, and electrochemical properties. As a technology demonstrator, the working electrodes of hydrogen peroxide (H2 O2 ) sensors fabricated from plasma‐reduced GO show a sensitivity of 277 ± 80 µA mm −1 cm −2, which is comparable to RGO working electrodes made by electrochemical reduction. Abstract : An inkjet printing of reduced graphene oxide (RGO) with excellent electrical, mechanical, and electrochemical properties is demonstrated by using GO flakes dispersed binder‐free in aqueous solutions followed by treatment with a nonthermal radio‐frequency (RF) plasma containing only argon (Ar) gas. This technique is friendly to temperature sensitive and moisture absorbent materials such as paper.